Isaac N. Phillips, The Revised Ordinances of the City of Bloomington 47 (1876) - (:unkn) unknown (My University, 1876)
Licenses, Division 11. Shooting Galleries, §1-3: Prohibited owning, keeping, or running any shooting gallery or target shooting without obtaining a license. Violators fined twenty-five dollars for each offense. Such licenses will last for one year and cost ten dollars or fifty cents per day.
Keywords: SHOOTING RANGES OR GALLERIES